Overdoping effect with Zr and Hf on the oxidation behaviour of FeCrAl-Hf by means of Atom Probe Tomography - Daradkeh, Samer I.; Recalde, Oscar; Mousa, Marwan S.; Sobola, Dinara (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
The study investigated the oxidation behaviour and grain boundary diffusion of minor/major elements of FeCrAl alloys, doped with over-critical concentrations of reactive elements (REs) Zr and Hf. While the formation of ?-Al2O3 scale on these alloys is conventionally attributed to inward oxygen transport along grain boundaries, this research proposes that metal ion outward diffusion also contributes to the development of oxide scales and their microstructural characteristics. Samples were analyzed after thermal exposure at 1100 °C using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atom probe tomography (APT). Results revealed increased oxide growth, deeper internal oxidation, and RE-oxide formation near and at oxide grain boundaries due to enhanced inward and outward diffusion resulting from overdoping. The impact of overdoping varied with RE type and concentration, influenced by solubility, ionic size, and electronic structure of alumina. Notably, Zr-doped samples maintained alumina adhesion to the alloy after thermal exposure, whereas severe spallation occurred in Hf-doped samples.
Keywords: Overdoping; Reactive element; Grain boundary; Alumina